SOFIA Observations of 30 Doradus. II. Magnetic Fields and Large-scale Gas Kinematics - Le Ngoc Tram; Lars Bonne; Yue Hu; Enrique Lopez-Rodriguez; Jordan A. Guerra; Pierre Lesaffre; Antoine Gusdorf; Thiem Hoang; Min-Young Lee; Alex Lazarian; B-G Andersson; Simon Coudé; et al. (The Astrophysical Journal, 2023)
The heart of the Large Magellanic Cloud, 30 Doradus, is a complex region with a clear core-halo structure. Feedback from the stellar cluster R136 has been shown to be the main source of energy creating multiple parsec-scale expanding-shells in the outer region, and carving a nebula core in the proximity of the ionization source. We present the morphology and strength of the magnetic fields ( B -fields) of 30 Doradus inferred from the far-infrared polarimetric observations by SOFIA/HAWC+ at 89, 154, and 214 μ m. The B -field morphology is complex, showing bending structures around R136. In addition, we use high spectral and angular resolution [C ii ] observations from SOFIA/GREAT and CO(2-1) from APEX. The kinematic structure of the region correlates with the B -field morphology and shows evidence of multiple expanding-shells. Our B -field strength maps, estimated using the Davis–Chandrasekhar–Fermi method and structure-function, show variations across the cloud within a maximum of 600, 450, and 350 μ G at 89, 154, and 214 μ m, respectively. We estimated that the majority of the 30 Doradus clouds are subcritical and sub-Alfvénic. The probability distribution function of the gas density shows that the turbulence is mainly compressively driven, while the plasma beta parameter indicates supersonic turbulence. We show that the B -field is sufficient to hold the cloud structure integrity under feedback from R136. We suggest that supersonic compressive turbulence enables the local gravitational collapse and triggers a new generation of stars to form. The velocity gradient technique using [C ii ] and CO(2-1) is likely to confirm these suggestions.